ОКАЗАНИЕ ВЫСОКОТЕХНОЛОГИЧНОЙ МЕДИЦИНСКОЙ ПОМОЩИ НА БАЗЕ ОБЛАСТНОЙ БОЛЬНИЦЫ В СЛОЖИВШЕЙСЯ ЭПИДЕМИОЛОГИЧЕСКОЙ СИТУАЦИИ - Набережная, Инна Борисовна; Захаров, Дмитрий Александрович; Захарова, Ульяна Дмитриевна; Аубекиров, Артур Рамилевич (FORCIPE, 2022)